ANALYSIS OF COMPANY STRATEGY USING THE BOSTON CONSULTING GROUP (BCG) MATRIX AT CV. TJAHAJA BARU - Mai Yuliza; Eko Putra; Elondri Elondri; Andi Pangestu (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The success of a company in achieving its business goals is closely related to its marketing capabilities as a vital department that interacts directly with consumers. Before formulating an effective strategy, a thorough analysis of the company is essential. A widely used company analysis approach is the BCG Growth/Share Matrix, pioneered by the Boston Consulting Group (BCG), a private management consulting firm headquartered in Boston, known for its expertise in market share development. This study examines the strategic positioning of CV. Tjahaja Baru Simpang Empat using the BCG Growth/Share Matrix. The company, a Yamaha motorcycle distributor, demonstrated a 10.7% sales market growth from 2021 to 2022. The relative market share of Yamaha increased from 0.17 to 0.32 within the same period. Despite this growth, the company's market share remains below one, suggesting room for improvement. CV. Tjahaja Baru Simpang Empat falls within the "Question Mark" quadrant, denoting high growth potential with low market share. A "Build" strategy is recommended, capitalizing on the growth opportunity to increase market share. This research underscores the significance of strategic planning, utilizing the BCG matrix to guide marketing strategies and enhance business success.